BIM + AR: Onsite information sharing and communication via advanced visualization - Wang, Xiangyu; Love, Peter (IEEE, 2012)
More and more design and construction professionals in Architecture, Engineering, and Construction (AEC) areas have been and now are using Building Information Modeling (BIM). Unfortunately, there were very few efforts exploring the real-time communication and integration of BIM to the site and task conditions, and the interaction of BIM with the field crew. It is envisaged that Augmented Reality (AR) can fulfil this vision effectively through visualizing BIM right into the physical context of each construction activity or task. This paper discusses and investigates how BIM can be extended to the site via the “practical arm” of AR. Human factors are the core principle to investigate on, considering that AR, by nature, involves the human sensations with both real and virtual information sources. It is also found that AR should be ubiquitous and work together with accurate positioning technologies such as laser pointing. The framework also addresses how context-aware can be implemented in the integration of BIM and AR to achieve intelligent AR.